Tuning the Transdermal Delivery of Hydroquinone upon Formulation with Novel Permeation Enhancers - Dolores R. Serrano; María José Gordo; Antonio Matji; Salvador González; Aikaterini Lalatsa; Juan José Torrado (MDPI AG, 2019)
Hydroquinone (HQ) is an anti-hyperpigmentation agent with poor physicochemical stability. HQ formulations are currently elaborated by compounding in local pharmacies. Variability in the characteristics of HQ topical formulations can lead to remarkable differences in terms of their stability, efficacy, and toxicity. Four different semisolid O/W formulations with 5% HQ were prepared using: (i) Beeler´s base plus antioxidants (F1), (ii) Beeler´s base and dimethyl isosorbide (DMI) as solubiliser (F2), (iii) olive oil and DMI (F3), and (iv) Nourivan®, a skin-moisturising and antioxidant base, along with DMI (F4). Amongst the four formulations, F3 showed the greatest physicochemical stability with less tendency to coalescence but with marked chromatic aberrations. An inverse correlation was established by multivariate analysis between the mean droplet size in volume and the steady-state flux, which explains why F3, with the smallest droplet size and the most hydrophobic excipients, exhibited the highest permeation across both types of membranes with enhancement ratios of 2.26 and 5.67-fold across Strat-M® and mouse skin, respectively, compared to F1. It is crucial to understand how the HQ is formulated, bearing in mind that the use of different excipients can tune the transdermal delivery of HQ significantly.